A DEBATE ON THE SIMILARITY OF PARTICLE SIZING RESULTS DERIVED FROM THE ANALYSIS OF FINEGRAINED SEDIMENTS BY TWO DIFFERENT INSTRUMENTATIONS - Iatrou, M.; Papatheodorou, G.; Piper, D. J.W.; Tripsanas, E.; Ferentinos, G. (Bulletin of the Geological Society of Greece, 2007)
A set of grab-sample sediments collected from the basin floor of the Corinth Gulf, Greece, was analysed using two different techniques; LS 230 laser system and Coulter Counter TA II. The present study presents the results derived from the comparison between the two techniques. The correlation between the mean size and the sorting values obtained from the two methods is moderate. Also moderate are the correlations estimated for the fractions of clay and silt obtained from the two methods Furthermore the analysis showed that the Laser Coulter determines coarser grain sizes than the Coulter. The analysis of variation/residuals within individual size intervals showed a higher variability of residuals for the coarser fractions (7-6 and 5-4 phi).